MICHEL DE MONTAIGNE: CREATOR OF RENAISSANCE PERIOD - Asror Muhamedov (Scholar Express Journal, 2024)
This article highlights the life and services of Michel Montaigne as a prominent figure in the Renaissance. This helps to demonstrate Montaigne’s influence on literature, philosophy, and the broad cultural landscape of the Renaissance by examining his role as a multifaceted thinker, writer, and philosopher. Highlighting Montaigne’s pioneering literary form, philosophical research, enduring influence, and his innovative ideas effectively reveal his status as a renaissance creator who continues to resonate across time and Sciences. The article analyzes the philosophical-ethical views of Michel Montaigne's work "Experiments" and their influence on the lifestyle of mankind today and their role in the formation of youth well-being. It was discussed how Michel Montaigne's views on society were important for the Renaissance period. Moreover, this article also examines the study of Michel Montaigne's work "Experiments" in the Western countries and its philosophical analysis.
Keywords: Renaissance; intellectual awakening; genre of essay